2018
DOI: 10.1016/j.devcel.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Dual Requirement of CHD8 for Chromatin Landscape Establishment and Histone Methyltransferase Recruitment to Promote CNS Myelination and Repair

Abstract: Disruptive mutations in chromatin remodeler CHD8 cause autism spectrum disorders, exhibiting widespread white matter abnormalities; however, the underlying mechanisms remain elusive. We show that cell-type specific Chd8 deletion in oligodendrocyte progenitors, but not in neurons, results in myelination defects, revealing a cell-intrinsic dependence on CHD8 for oligodendrocyte lineage development, myelination and post-injury remyelination. CHD8 activates expression of BRG1-associated SWI/SNF complexes that in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
142
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(153 citation statements)
references
References 69 publications
8
142
3
Order By: Relevance
“…This partial requirement of Chd7 during differentiation/maturation of Chd7 -deficient OPCs result at least in part from a functional compensation provided by Chd8 which, like Chd7, binds to the majority of OL differentiation genes in OPCs. Together with our previous report on Chd7 expression during OL differentiation and myelination ( 28 ), and our complementary study on Chd8 LOF in OL lineage cells ( 37 ), the present results underscore CHD chromatin remodelers as key regulators of the progression along the differentiation/maturation pathway in OL lineage cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This partial requirement of Chd7 during differentiation/maturation of Chd7 -deficient OPCs result at least in part from a functional compensation provided by Chd8 which, like Chd7, binds to the majority of OL differentiation genes in OPCs. Together with our previous report on Chd7 expression during OL differentiation and myelination ( 28 ), and our complementary study on Chd8 LOF in OL lineage cells ( 37 ), the present results underscore CHD chromatin remodelers as key regulators of the progression along the differentiation/maturation pathway in OL lineage cells.…”
Section: Discussionsupporting
confidence: 88%
“…Given that we integrated ChIP-seq datasets obtained from rat and mouse, we asked whether binding is conserved between species. To address this question, we compared the Chd8-binding profile between our in vivo mouse-purified O4 + cells with rat OPC primary cultures ( 37 ) and observed a large overlap (87%) ( SI Appendix , Fig. S5 B ) of bound genes between species, comparable to the reported overlap of Chd8 ChIP-seq replicates from the same sample ( 36 , 38 ).…”
Section: Resultsmentioning
confidence: 71%
“…One of the risk genes, Chd8, encodes a protein that binds directly to b-catenin and negatively regulates the Wnt signaling pathway, which plays a crucial role in progenitor proliferation and differentiation in the forebrain (Sakamoto et al, 2000;Durak et al, 2016;Katayama et al, 2016;Platt et al, 2017). Our results showed that Chd8 modulates gene programs for oligodendrocyte differentiation and maturation, consistent with previously reported ChIP-Seq results showing that CHD8 interacts directly with OPC maturation genes in the neonatal stage Zhao et al, 2018). Other cell types may be altered at different developmental stages, through cell-autonomous (intrinsic) or non-cell autonomous (extrinsic) mechanisms, which should be investigated further in the future.…”
Section: Discussionsupporting
confidence: 91%
“…The variability in behavioral phenotypes between the different Chd8 mutant lines also calls into question the generalizability of the cellular and molecular phenotypes reported in other studies. However, important discoveries have been made that indicate a possible mechanism linking Chd8 deficiency to altered behavior, including delayed neurodevelopment [Katayama et al, 2016], myelination defects [Zhao et al, 2018], increased proliferation of neuronal progenitors [Gompers et al, 2017], increased total brain volume and volumetric increases of several brain regions [Suetterlin et al, 2018], and changes in inhibitory synaptic transmission [Jung et al, 2018]. Side-by-side comparisons of the different mutant lines could be informative after a more complete understanding of the transcriptional regulation of CHD8 is obtained.…”
Section: Discussionmentioning
confidence: 99%